Settling for Less: Do Statoliths Modulate Gravity Perception? - Ditengou, Franck Anicet (Plants (Basel), 2020)
Plants orientate their growth either towards (in roots) or away from (in shoots) the Earth’s gravitational field. While we are now starting to understand the molecular architecture of these gravity response pathways, the gravity receptor remains elusive. This perspective looks at the biology of statoliths and suggests it is conceivable that their immediate environment may be tuned to modulate the strength of the gravity response. It then suggests how mutant screens could use this hypothesis to identify the gravity receptor.